2021
DOI: 10.1038/s41598-021-89561-1
|View full text |Cite
|
Sign up to set email alerts
|

A nickel phosphide nanoalloy catalyst for the C-3 alkylation of oxindoles with alcohols

Abstract: Although transition metal phosphides are well studied as electrocatalysts and hydrotreating catalysts, the application of metal phosphides in organic synthesis is rare, and cooperative catalysis between metal phosphides and supports remains unexplored. Herein, we report that a cerium dioxide-supported nickel phosphide nanoalloy (nano-Ni2P/CeO2) efficiently promoted the C-3 alkylation of oxindoles with alcohols without any additives through the borrowing hydrogen methodology. Oxindoles were alkylated with vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 76 publications
0
24
0
Order By: Relevance
“…In this respect, the direct C-alkylation of indoles with alcohols by socalled catalytic 'borrowing hydrogen (BH) methodology' or "hydrogen autotransfer" reaction is a more suitable methodology with water as the only by-product. [18][19][20][21][22][23] In general, the C3-alkylation of indoles with alcohols involves the following steps (Scheme 1): (i) acceptorless dehydrogenation of alcohol to the corresponding aldehyde, (ii) nucleophilic addition of an alkylideneindolenine formation to the aldehyde and elimination of water. Finally, in situ hydro- Following the BH strategy, Grigg pioneered the C3-alkylation of indoles with benzyl alcohols as the alkyl source in the presence of [Cp*IrCl 2 ] 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, the direct C-alkylation of indoles with alcohols by socalled catalytic 'borrowing hydrogen (BH) methodology' or "hydrogen autotransfer" reaction is a more suitable methodology with water as the only by-product. [18][19][20][21][22][23] In general, the C3-alkylation of indoles with alcohols involves the following steps (Scheme 1): (i) acceptorless dehydrogenation of alcohol to the corresponding aldehyde, (ii) nucleophilic addition of an alkylideneindolenine formation to the aldehyde and elimination of water. Finally, in situ hydro- Following the BH strategy, Grigg pioneered the C3-alkylation of indoles with benzyl alcohols as the alkyl source in the presence of [Cp*IrCl 2 ] 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the direct C-alkylation of indoles with alcohols by so-called catalytic ‘borrowing hydrogen (BH) methodology’ or “hydrogen autotransfer” reaction is a more suitable methodology with water as the only by-product. 18–23…”
Section: Introductionmentioning
confidence: 99%
“… 9 13 Our group recently reported the unique catalytic properties exhibited by nonprecious metal phosphide (Ni 2 P and Co 2 P) NPs in selective liquid-phase molecular transformations, e.g., the transformation of biomass-derived molecules; 14 18 the hydrogenation of nitriles, carbonyls, nitroarenes, and sulfoxides; 19 22 the reductive amination of carbonyls; 23 and the alkylation of oxindoles. 24 These studies revealed the potential of nonprecious metal phosphide NPs to serve as a novel class of highly efficient heterogeneous catalysts for versatile liquid-phase reactions, outperforming conventional single nonprecious metal NPs. These results motivated us to study the catalytic properties of precious metal phosphides for organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting metal–metal nanoalloy catalysts have been widely studied and have delivered great benefits in diverse fields, including automobile exhaust cleaning, energy conversion, and industrially important reactions like petroleum reforming and fine chemical synthesis. Compared to metal–metal nanoalloys, the catalytic effect of incorporating nonmetals into metal NPs has not been widely explored. Among metal–nonmetal alloy catalysts, metal phosphide NPs have attracted increased attention as hydrotreating catalysts and electrocatalysts. However, despite their unique properties the use of metal phosphide catalysts in organic syntheses has rarely been investigated. Our group recently reported the unique catalytic properties exhibited by nonprecious metal phosphide (Ni 2 P and Co 2 P) NPs in selective liquid-phase molecular transformations, e.g., the transformation of biomass-derived molecules; the hydrogenation of nitriles, carbonyls, nitroarenes, and sulfoxides; the reductive amination of carbonyls; and the alkylation of oxindoles . These studies revealed the potential of nonprecious metal phosphide NPs to serve as a novel class of highly efficient heterogeneous catalysts for versatile liquid-phase reactions, outperforming conventional single nonprecious metal NPs.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, two examples basing on Ni catalysis were consequently demonstrated by Balaraman and Tang groups . Meanwhile, activated amides, such as oxindole and 4-hydroxy-quinolone, were also explored to undergo α-alkylation with alcohols via a BH strategy; however, these protocols are limited to activated cyclic amide derivatives.…”
Section: Introductionmentioning
confidence: 99%